Analytical techniques for characterizing cyclodextrins and their inclusion complexes with large and small molecular weight guest molecules. (September 2017) - Narayanan, Ganesh; Boy, Ramiz; Gupta, Bhupender S.; Tonelli, Alan E.
Abstract: Cyclodextrins are oligosaccharides that have truncated cone like structures, making them capable of forming non-covalent bonds with a large variety of molecules (especially hydrophobic molecules). Additionally, as the outer rims of their truncated cones are lined with several hydroxyl groups, secondary interactions with and functionalization of these hydroxyl groups are also possible. Current techniques available to analyze and characterize these interactions, although somewhat limited, can be accomplished by judicious selection of analytical tools. However, for emerging applications, the currently utilized techniques summarized in this review may not be sufficient. The purpose of this review is to provide an overview, including their possible limitations, of current techniques commonly employed to investigate such interactions. In view of CD-based materials for emerging applications, wherever possible, analytical tools used for these studies are also discussed.